2021
DOI: 10.1186/s12920-021-01125-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing identified the ceRNA network associated with recurrent spontaneous abortion

Abstract: Background Recurrent spontaneous abortion (RSA) is one of the common complication of pregnancy, bringing heavy burden to the patients and their families. The study aimed to explore the lncRNA-miRNA-mRNA network associated with recurrent spontaneous abortion. Methods By transcriptome sequencing, we detected differences in lncRNA, miRNA and mRNA expression in villus tissue samples collected from 3 patients with RSA and 3 normal abortion patients. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Recurrent spontaneous abortion ANRIL decreases (122) Recurrent spontaneous abortion PVT1 decreases (122) Recurrent spontaneous abortion HOTAIR decreases (121) Recurrent spontaneous abortion SNHG5 decreases (119) Recurrent spontaneous abortion H19 increases (113) Recurrent spontaneous abortion MEG8 increases (122) Recurrent spontaneous abortion LINC01088 increases…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent spontaneous abortion ANRIL decreases (122) Recurrent spontaneous abortion PVT1 decreases (122) Recurrent spontaneous abortion HOTAIR decreases (121) Recurrent spontaneous abortion SNHG5 decreases (119) Recurrent spontaneous abortion H19 increases (113) Recurrent spontaneous abortion MEG8 increases (122) Recurrent spontaneous abortion LINC01088 increases…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that mRNA regulated URSA via multiple signaling pathways, including antigen processing and presentation, the Toll-like receptor signaling pathway, and Natural killer cell mediated cytotoxicity. Classically, activated macrophages in decidua are mainly involved in antigen processing and presentation ( Li et al, 2021 ) which has been shown to be associated with URSA ( Huang et al, 2021 ). Toll like receptors are a family of pattern recognition receptors, which play an essential role in maintaining innate host immunity and Th1/Th2 balance ( Koga and Mor, 2010 ; Chen et al, 2016 ), thereby permitting and accepting implanted and growing semi allogenic embryos.…”
Section: Discussionmentioning
confidence: 99%
“…The lnc-SLC4A1-1 gene was discovered to be significantly expressed in the villi of URSA patients and to be able to trigger an immunological response via the NF-B/CXCL8 axis (117). In peripheral blood mononuclear cells from pregnant women with URSA, the expression levels of the lncRNAs SNHG5 and KLF4 were aberrant, and both of these were risk factors for the development of URSA (118,119). We discovered that the lncRNA types HOTAIR and SNHG7 are related to recurrent spontaneous abortion pathogenesis and control trophoblast proliferation, apoptosis, invasion, and chorionic villus angiogenesis (120,121).…”
Section: Exosomal Lncrna Offers Fresh Approaches To Identifying and T...mentioning
confidence: 99%